2010
DOI: 10.1007/s11468-010-9136-9
|View full text |Cite
|
Sign up to set email alerts
|

Luminescence Study of Silver Nanoparticles Obtained by Annealed Ionic Exchange Silicate Glasses

Abstract: The photoluminescence of silver nanoparticles glasses obtained by ionic exchange and annealing is investigated for various ionic exchange times. These glasses are prepared by immersion of silicate glass samples in a molten salt bath of molar concentration 10% AgNO 3 in NaNO 3 at T=320°C. Scanning electron microscopy measurement in electron diffraction scattering (EDS) configuration confirms the silver presence in the various glasses, and the UV/visible absorption gives the evolution of the spectra after ionic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 22 publications
(11 reference statements)
2
8
0
Order By: Relevance
“…However, PL from metal NPs (NPs) has not been studied thoroughly, partly due to the low probability of corresponding radiative transitions in the metals noted above. The PL of noble metal NPs has been reported for Ag [62][63][64][65], Au [66,67], and Cu [68,69]. Each of these studies revealed a maximum of the PL band close to the interband absorption edge, so the PL was attributed to the interband radiative transitions.…”
Section: Introductionmentioning
confidence: 95%
“…However, PL from metal NPs (NPs) has not been studied thoroughly, partly due to the low probability of corresponding radiative transitions in the metals noted above. The PL of noble metal NPs has been reported for Ag [62][63][64][65], Au [66,67], and Cu [68,69]. Each of these studies revealed a maximum of the PL band close to the interband absorption edge, so the PL was attributed to the interband radiative transitions.…”
Section: Introductionmentioning
confidence: 95%
“…Second term c eÀe in Eq. (5), the rate of electron-electron scattering is expressed as the sum of the temperature dependent and the frequency dependent terms 52 c eÀe ðx; TÞ ¼ c T e ðTÞ þ c f e ðxÞ; (8) where c T e ðTÞ ( c eÀph and, correspondingly, is neglected in our calculations, while frequency dependent term is expressed as 53…”
Section: Theoretical Model and Calculationsmentioning
confidence: 99%
“…The PL from metal nanoparticles (NPs) has not been studied much as well, partly because of the very low probability of corresponding radiative transitions in the metals noted above. The PL of noble metal NPs has been reported for silver, [6][7][8][9] gold, 10,11 and copper. 12,13 All these studies revealed the maximum of the PL band close to the interband absorption edge and, thus, the PL was attributed to the interband radiative transitions.…”
mentioning
confidence: 99%
“…Optical properties of these different ionic silver species in silver ion-exchanged glasses have been widely studied because they lead to a novel broad emission, covering 350 nm to 610 nm. [17][18][19][20][21][22][23] In fact, the outermost electron 4d 10 -4d 9 5s 1 transitions of silver ions give rise to typical luminescence features whose shape and position depend on the local ion environment and on the formation of aggregates or dimers in the glass matrix. 19 In particular, four main features have been identified: a UV band around 350 nm, which is attributed to Ag þ spin-allowed transitions from the 1 D 2 state to the 1 S 0 ground state under about 250 nm excitation; 23 a violet band at about 420 nm, which is attributed to Ag þ spin-forbidden transitions of the type 3 D 1À3 -1 S 0 ; 19,21 a deep-blue band at about 450 nm attributed to (Ag 2 ) þ ; 11,18,20,24 and a green band at about 525 nm attributed to Ag þ -Ag þ pairs.…”
mentioning
confidence: 99%
“…19 In particular, four main features have been identified: a UV band around 350 nm, which is attributed to Ag þ spin-allowed transitions from the 1 D 2 state to the 1 S 0 ground state under about 250 nm excitation; 23 a violet band at about 420 nm, which is attributed to Ag þ spin-forbidden transitions of the type 3 D 1À3 -1 S 0 ; 19,21 a deep-blue band at about 450 nm attributed to (Ag 2 ) þ ; 11,18,20,24 and a green band at about 525 nm attributed to Ag þ -Ag þ pairs. 11,17,19,22,24 The excitation source that could be used to generate blue and green emission is about 350 nm UV light. In the early literature, 23 the bluer/green band emission is assigned to spin-forbidden transitions from the 3 D manifold to the ground state.…”
mentioning
confidence: 99%